Sclerotinia rot of Zephyranthes candida caused by Sclerotinia sclerotiorum and Sclerotinia minor - Yin, Fuqiang; Song, Zhen; Liu, Lu; Xu, Qin; Jiang, Jiamin; Xiao, Zhien; Guo, Tiantian; Liu, Yuxin; Zhang, Shaotian; Yuan, Yue; Ma, Wanli; Liu, Ming (Frontiers in Microbiology, 2024)
sclerotinia rot is a serious disease that occurs on Zephyranthes candida. A thorough understanding of the pathogenic fungal species and understanding the biological characteristics are important for controlling sclerotinia. Fungal strains were isolated from the diseased leaves of Z. candida through tissue isolation. Koch's hypothesis screened pathogenic strains by pathogenicity of healthy leaves, including re-isolation and identification. A multigene phylogenetic tree was constructed by extracting genomic DNA from pathogenic strains and measuring the nucleotide sequences at four sites, including the internal transcribed spacer (ITS), RNA polymerase II second largest subunit (RPB2), glyceraldehyde-3-phosphate dehydrogenase (G3PDH), and heat shock protein 60 (HSP60). Morphological characteristics of the fungal structures were evaluated through microscopic analysis.The growth of pathogens was observed and recorded under different pH, different temperatures, different carbon sources and different nitrogen sources to clarify their biological characteristics.Representative strains D7, D13, X4, and X15 infected Z. candida and caused sclerotinia rot. At the beginning of the culture, white flocculent fungal hyphae appeared on the potato dextrose agar (PDA) medium, and black spherical to irregular-shaped sclerotia appeared at the edge of the colony after 7 days. The diameter of the sclerotia was 2.4-8.6 mm and 0.4-0.9 mm, respectively. One sclerotium was able to germinate from 1-5 apothecia. Ascus were cylindrical or spindle-shaped, with a size of 110.0-120.0 × 9.2-11.6 μm. One ascus contained eight colorless, oval ascospores, with a size of 8.4-12.0 × 4.5-5.5 μm. Based on the phylogenetic tree constructed with the gene sequences for ITS, G3PDH, HSP60, and RPB2, D7 and D13 shared 99% homology with sclerotinia sclerotiorum, whereas X4 and X15 shared 99% homology with sclerotinia minor. S. sclerotiorum growth was more suitable when the culture temperature was 15℃-25℃, pH 5.0, carbon source was maltose and nitrogen source was yeast powder. S. minor growth was more suitable when the culture temperature was 15℃, pH 5.0, the carbon source was glucose, and the nitrogen source was yeast powder. The results identified the pathogens as S. sclerotiorum and S. minor. To the best of our knowledge, this is